Implikasi Religiusitas Pementasan Tari Sanghyang Jaran di Desa Bungkulan pada Masa Pandemi Covid 19 - Kusuma, Afnan Dzanu; Aliffiati, .; Kaler, I Ketut (Sunari Penjor : Journal of Anthropology, 2023)
During the COVID-19 pandemic, the performance of the Sanghyang Jaran Dance in Bungkulan Village was delayed several times. The delay in the performance of this sacred dance ultimately has implications for the religious values ??of the adherents. This paper aims to identify the religious implications of the postponement of the Sanghyang Jaran dance performance. Kontjaraningrat and Robertson Smith's religious theory was used to interpret the data obtained. The results of the study indicate that there are at least three forms of religiosity implications experienced by the community during the postponement. First, the dancers are often visited by the spirit of Sanghyang Jaran in an unusual or angry condition. In addition, the dancer's family also experienced unusual illness and frequent household problems. Second, farmers experience anxiety due to declining yields and thefts that have occurred several times. Third, people experience discomfort with the surrounding conditions such as tense, many people are sick, so many people die in a row in the near future or grubug.